Digital Game Based Learning Tebak Nama Buah dan Sayuran Dalam Bahasa Inggris Dengan Model Addie - Indarti Indarti; Dewi Laraswati (Universitas Bina Sarana Informatika, 2021)
Learning in the pademi craves the more creativity from in making the learning methods he continued to shiva learning it not bored or being passive therapy enthusiastic learning in higher.Digital games based learning (DGBL) model learning based digital game so that children. more interactive Method of development learning based game or games based learning can use analyzing, addie was or designing, developing, implementing and evaluating.